2021
DOI: 10.4102/hsag.v26i0.1586
|View full text |Cite
|
Sign up to set email alerts
|

Coping mechanisms used by the families of mental health care users in Mahikeng sub-district, North West province

Abstract: Background: Families of the mental health care users (MHCUs) face different challenges in dealing with, supporting and caring for MHCUs on a daily basis. The divergent coping mechanisms that the family members use aim to lower the negative, psychological and emotional impact of the stress. These include: escape, avoidance and denial.Aim: To explore, describe and contextualise coping mechanisms used by the families of MHCUs and to suggest recommendations for improving their coping mechanisms in Mahikeng sub-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…In a study by Pusey-Murray and Miller ( 2013 :119), family members reported that mentally ill patients sometimes refused to take their medication as prescribed; unpleasant side effects and a lack of insight were the primary reasons for this. This is similar to a South African study by Modise et al ( 2021 :5–6) who mentioned defaulting on medication as challenge family members of psychiatric patients were facing which led to aggression, unpredictable behaviour, stigma and discrimination by the community. Moreover, this was also reported by Von Kardoff et al ( 2016 :4), stating medication compliance was one of the problems reported by their participants.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In a study by Pusey-Murray and Miller ( 2013 :119), family members reported that mentally ill patients sometimes refused to take their medication as prescribed; unpleasant side effects and a lack of insight were the primary reasons for this. This is similar to a South African study by Modise et al ( 2021 :5–6) who mentioned defaulting on medication as challenge family members of psychiatric patients were facing which led to aggression, unpredictable behaviour, stigma and discrimination by the community. Moreover, this was also reported by Von Kardoff et al ( 2016 :4), stating medication compliance was one of the problems reported by their participants.…”
Section: Discussionsupporting
confidence: 89%
“…It may have a negative impact on family relationships, finances, physical and psychological well-being of family members in terms of decreasing the quality of life of individuals caring for a sibling with mental illness. Modise et al ( 2021 :7) found that family members in their study experienced diverse challenges which included aggression from their mentally ill relatives, stigma from the community as well as negative attitudes from the nursing staff.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in this study sometimes went as far as borrowing money from loan sharks so that they could give their relatives whatever they demanded. This is supported by a study conducted by Modise, Mokgaola and Sehularo ( 2021 :6); the researchers stated that participants reported that their salary was not enough to take care of the basic needs of the mental healthcare user (MHCU).…”
Section: Discussion Of Findingsmentioning
confidence: 86%
“…Family involvement is a significant factor in the treatment and recovery of patients with mental illness, as mental health problems have been associated with an assortment of social and psychological processes in one’s family and family involvements have been reported to help with relapse prevention and reduced hospital stays for mental health users [ 1 , 2 , 3 ]. However, caring for mental health care users (MHCUs) is associated with great psychological and psychiatric morbidity for the family members themselves [ 4 ]. Families with MHCUs experience a range of negative emotional states that include irritation and frustration when they think of their loved ones with mental illness.…”
Section: Introductionmentioning
confidence: 99%